Places of learning: Media, architecture, pedagogy - Ellsworth, Elizabeth (RoutledgeFalmer, 2005)
This book takes a close look at places of learning located outside of schools, yet deeply concerned with the experience of the learning self. It explores what it might mean to think of pedagogy not in relation to knowledge as a "thing made," but to knowledge in the making.